Three-dimensional crustal and upper mantle P-wave velocity model and Moho map of Finland constructed by kriging interpolation - Kolehmainen, Kauri (Helsingin yliopisto, 2023)
A new three-dimensional crustal and upper mantle P-wave velocity model and a Moho depth map of Finland and the surrounding area were constructed using kriging interpolation. The models are based on the latest wide-angle reflection and refraction (WARR) data from the Fennoscandian shield. The Moho depth map agrees with previous Moho maps but also shows new details in the large Moho depression in central Finland compared to the previous Moho maps. The new Moho features include a new Moho depth local maximum near the center of the depression and increased Moho depths extending to the northwest and south of the depression. The three-dimensional crustal and upper mantle P-wave velocity model differs from previous models by showing a non-existent high-velocity lower crust beneath the Wiborg Rapakivi Batholith. Both the Moho map and the velocity model exhibit distinct features within the tectonic provinces in the Fennoscandian Shield. The uppermost velocity model layer is shown to roughly correlate with general features of surface geology. Statistical analysis of Moho depth and P-wave velocity data was performed, and variogram models were fitted to capture spatial autocorrelation. Ordinary kriging was used to generate a Moho model with a 25 × 25 km grid cell size. The three-dimensional P-wave velocity model was constructed in two parts, with separate universal kriging schemes for the crustal and upper mantle velocities. The velocity model has a grid cell size of 50 × 50 × 1 km in the uppermost 4 km and a lower resolution of 50 × 50 × 2 km below 4 km depth. The presented models can be utilized for a variety of applications, including seismic source location, crustal effect correction for seismic tomography and teleseismic studies, and general modeling of large-scale tectonic processes.